The Portal of Geriatrics Online Education: A 21st‐Century Resource for Teaching Geriatrics. Issue 2 (30th January 2015) - Ramaswamy, Ravishankar; Leipzig, Rosanne M.; Howe, Carol L.; Sauvigne, Karen; Usiak, Craig; Soriano, Rainier P.
<x xml:space="preserve">Abstract</x> The way students are taught and evaluated is changing, with greater emphasis on flexible, individualized, learner‐centered education, including the use of technology. The goal of assessment is also shifting from what students know to how they perform in practice settings. Developing educational materials for teaching in these ways is time‐consuming and can be expensive. The Portal of Geriatrics Online Education (POGOe) was developed to aid educators in meeting these needs and become quicker, better‐prepared teachers of geriatrics. POGOe contains more than 950 geriatrics educational materials that faculty at 45% of allopathic and 7% of osteopathic U.S. medical schools and the Centers for Geriatric Nursing Excellence have created. These materials include various instructional and assessment methodologies, including virtual and standardized patients, games, tutorials, case‐based teaching, self‐directed learning, and traditional lectures. Materials with common goals and resource types are available as selected educational series. Learner assessments comprise approximately 10% of the educational materials. POGOe also includes libraries of videos, images, and questions extracted from its educational materials to encourage educators to repurpose content components to create new resources and to align their teaching better with their learners' needs. Web‐Geriatric Education Modules, a peer‐reviewed online modular curriculum for medical students, is a prime example of this repurposing. The existence of a robust compendium of instructional and assessment materials allows educators to concentrate more on improving learner performance in practice and not simply on knowledge acquisition. It also makes it easier for nongeriatricians to teach the care of older adults in their respective disciplines.